2023
DOI: 10.1088/1402-4896/ad075c
|View full text |Cite
|
Sign up to set email alerts
|

Quantum controlled teleportation with OR-logic-gate-like controllers in noisy environment

Muhammad Taufiqi,
Lila Yuwana,
Agus Purwanto
et al.

Abstract: We evaluate a one-way, bidirectional, and cyclic quantum controlled teleportation with two controllers. We show that the controllers' agreement mimics the OR logic gate, i.e., the teleportation succeeds with only one of the controllers' cooperation, and it does not matter which one. This result is generalized to multi-ways quantum controlled teleportation with N controllers. The proposed protocols are evaluated by considering a noisy environment in the form of phase-damping noise and amplitude-damping noise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Lastly, in terms of channel preparation, we constructed the channel differently. A controller ability of the channel preparation in the common controlled protocols [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] is done by preparing a single qubit pure state and performing a combination of CNOT and Hadamard gates (sometimes with other additional gates). In our work, rather than preparing a pure state, we prepared a mixed state and perform CNOT gates (without any Hadamard gate, see section 2).…”
Section: A B B a B A D B E E B E B D E A A E A E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, in terms of channel preparation, we constructed the channel differently. A controller ability of the channel preparation in the common controlled protocols [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] is done by preparing a single qubit pure state and performing a combination of CNOT and Hadamard gates (sometimes with other additional gates). In our work, rather than preparing a pure state, we prepared a mixed state and perform CNOT gates (without any Hadamard gate, see section 2).…”
Section: A B B a B A D B E E B E B D E A A E A E Dmentioning
confidence: 99%
“…It was proposed by Sang et al [4] who used a seven-qubit entangled state as the quantum channel. Further studies on the protocol variation can be found in [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%